Characteristics of Gel from the Meat of Twelve Species of Fish from Visakhapatnam Coast - R., Chakrabarti; Gupta, Sibsankar (Fishery Technology, 2025)
Proximate composition and gel formation capacity of the meat from twelve low priced fish of Visakhapatnam coast were studied. It was found that the mince from these fish, on steaming formed gel having satisfactory strength. Gel strength of meat samples from fresh fish varied from 450 to -500 gem. The colour of the steamed cake from jew fish, bull's eye, barracuda and lizard fsh was white and it varied from light grey or yellow to grey in the case of goat fish, sardine, rainbow sardine, thread fin trevelly, horse mackerel, cat fish and scad. The fish mince from all the twelve species can be used for preparation of various products.